Characteristics of Myopia in Children at Prof. Dr. I.G.N.G. Ngoerah General Hospital Period 2020/2021 - Desriyanti, Putri Tamia; Surasmiati, Ni Made Ayu; Ratna Suryaningrum, I Gusti Ayu; Kusumadjaja, I Made Agus (E-Jurnal Medika Udayana; Vol 12 No 12 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i12.P05, 2023)
Myopia is the main cause of visual impairment suffered by school-age children in the world. Myopia causes children unable to see clearly at a distance so that if not corrected it can affect children's activities and achievements. This study aims to determine the characteristics of myopia in pediatric patients who came at Eye Polyclinic Prof. Dr. I.G.N.G. Ngoerah in 2020/2021. This study is a descriptive retrospective cross-sectional design with total sampling from secondary medical record which analyzed and processed using SPSS. Based on the study results, it was found that 32 pediatric patients suffered myopia. The results showed that myopia was more common in women (59.4%) with an age range 6-12 years (62.5%). Most of the patients were from Denpasar (62.5%). All cases of myopia were present in both eyes or bilateral (100.0%). The most common classification of myopia found compound myopic astigmatism in right eye (53.1%) and left eye (65.6%). Patients most often experienced moderate visual impairment with visual acuity <6/18 – 6/60 in right eye (46.9%) and left eye (40.6%). The highest degree of myopia was low myopia (40.6%) in right eye with a correction lens <S-3.00 and high myopia in left eye (43.8%) with >S-6.00. Most of patients experienced improvement to normal vision 6/6 – 6/12 after correction in right eye (59.4%) and left eye (65.6%). Amblyopia was found       (56.3%) myopia in children. The results of this study are expected to be basis for further research and to realize the importance of preventing and proper management myopia in children. Keywords: Myopia, school-age children, visual acuity, degree of myopia, post-correction visual acuity.